Influence of stable iodine on the uptake of the thyroid – model vs. experiment - Weber, K.; Wellner, U.; Voth, E.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: The influence of physiological and pharmacological amounts of iodine on the uptake of radioiodine in the thyroid was examined in a 4-compartment model. This model allows equations to be derived describing the distribution of tracer iodine as a function of time. The aim of the study was to compare the predictions of the model with experimental data. Methods: Five euthyroid persons received stable iodine (200 μg, 10 mg). 1-123-uptake into the thyroid was measured with the Nal (Tl)-detector of a body counter under physiological conditions and after application of each dose of additional iodine. Actual measurements and predicted values were compared, taking into account the individual iodine supply as estimated from the thyroid uptake under physiological conditions and data from the literature. Results: Thyroid iodine uptake decreased from 80% under physiological conditions to 50% in individuals with very low iodine supply (15 μg/d) (n = 2). The uptake calculated from the model was 36%. Iodine uptake into the thyroid did not decrease in individuals with typical iodine supply, i.e. for Cologne 65-85 μg/d (n = 3). After application of 10 mg of stable iodine, uptake into the thyroid decreased in all individuals to about 5%, in accordance with the model calculations. Conclusion: Comparison of theoretical predictions with the measured values demonstrated that the model tested is well suited for describing the time course of iodine distribution and uptake within the body. It can now be used to study aspects of iodine metabolism relevant to the pharmacological administration of iodine which cannot be investigated experimentally in humans for ethical and technical reasons.
Keywords: Iodine metabolism; iodine uptake; iodine supply; iodine prophylaxis; modelling